A Comparison of the Reactivity of Two Platinum Catalysts for Silicone Polymer Cross‐Linking by UV‐Activated Hydrosilation Reaction. Issue 4 (7th April 2015) - Marchi, Sophie; Sangermano, Marco; Meier, Patrick; Kornmann, Xavier
<x xml:space="preserve">Abstract</x> The synthesis of silicon compounds is mainly achieved by room temperature or high‐temperature vulcanization reaction. Several transition‐metal organometallic compounds such as platinum complexes can be used as catalysts to accelerate the thermal reaction. Moreover, these compounds are found to be also efficient for the cross‐linking of silicone polymer by UV‐activated reaction. In particular, cyclopentadienyl platinum complexes are considered as catalysts that can sustain an extremely high photochemical reaction after UV‐light excitation. The reactivity of these catalysts (in particular the trimethyl(methylcyclopentadienyl) (IV) complex (Me‐Cp)Pt(Me)3) for the photopolymerization of silicon polymer compounds is evaluated and compared with the most common bis(acetylacetonate)platinum (II) catalyst used for the UV‐activated hydrosilation reaction.<inline-graphic xlink:href="ark:/27927/pgj2fh7xr69" content-type="mren201500005-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />